Recurrence of Epidural Spinal Sarcoidosis. (July 2021) - Magdon, Louis A.; Elliott, Robin; Cheng, Christina W.
Abstract : Neurosarcoidosis involving the spine is uncommon. Sarcoidosis of the spine usually presents as an intramedullary lesion and rarely an epidural lesion. To have recurrence of neurosarcoidosis is an even rarer presentation. Here, we present a 37-year-old man with poorly controlled sarcoidosis who initially presented to our medical center in 2015 with thoracic myelopathy from epidural spinal sarcoidosis treated with thoracic decompression and fusion. He presented to the hospital 5 years later with a month history of progressive upper extremity weakness. MRI revealed recurrent stenosis and spinal cord compression in the cervicothoracic junction. Urgent surgical intervention along with medical management resulted in symptomatic and functional improvement. Surgical intervention and compliance with postoperative corticosteroid therapy seem to yield a favorable prognosis for patients with epidural spinal sarcoidosis and to avoid recurrence.